Gas Turbine Engine Performance Deterioration Modelling and Analysis - Singh Grewal, M. (Cranfield University, 1988)
In-service performance deterioration of gas turbine engines can be identified, at the engine module level, in terms of reductions in the component mass flow and the efficiency. Continued operation of a deteriorated gas turbine is (i) uneconomical and (ii) unsafe. Timely identification of the faults and ensuing maintenance could prevent both. Gas Path Analysis is a technique to establish the current performance level of the gas turbines and identify the faulty modules. Computer models can predict the off_design performance of gas turbines by aero-thermo-dynamically matching the engine components. This thesis describes the development of DETEM (DEeteriorated Turbine Engine Model), a generalised computer program, developed to model degraded gas turbine engines and analyse faults. The program has an integrated graphics module and creates windows on the VDU terminal,for displaying the program output and accepting the user input. This enables the user to compare the results of two different types of runs at the same time. The program incorporates sensor models that modify the output, with noise and in bias, based on the sensor characteristics, thus simulating a real engine. It is possible to simulate the engine performance at design point, off-design and under transient conditions. The runs could be for a "clean" and a deteriorated engine. Three techniques, iterative, fault coefficient matrix, and a statistical best-estimation technique, have been used to analyse the engine performance and identify the fault. Analysis of two and three shaft turbo-shaft engines and two spool turbo-fan and turbo-jet engines have been worked out in the thesis. Effects of reducing the number of measurements and measuring different engine parameters, on the accuracy of the fault identification, have been studied. The program is considered to have a potential for the generation of fault trees for rule-based expert system applied to gas turbine diagnostics. Because of the controlled output to the screen, a direct comparison of two different runs side by side, on the same screen, makes the program a good teaching aid for gas turbine diagnostics.